2016
DOI: 10.1186/s12872-016-0300-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of hypertension and hyperlipidemia in Izhevsk, Russia

Abstract: BackgroundCardiovascular disease (CVD) is the leading cause of death in Russia. Hypertension and hyperlipidemia are important risk factors for CVD that are modifiable by pharmacological treatment and life-style changes. We aimed to characterize the extent of the problem in a typical Russian city by examining the prevalence, treatment and control rates of hypertension and hyperlipidemia and investigating whether the specific pharmacological regimes used were comparable with guidelines from a country with much l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
2
10
2
Order By: Relevance
“…Relatively low levels of adherence were observed in most studies [11, 20, 22, 23, 31, 32, 37, 40, 41]. These findings are consistent with a cross-sectional study by Cybulsky et al on 1068 working-age men in Izhevsk, Russia, which reported 41% of patients taking antihypertensive drugs daily [43].…”
Section: Discussionsupporting
confidence: 80%
“…Relatively low levels of adherence were observed in most studies [11, 20, 22, 23, 31, 32, 37, 40, 41]. These findings are consistent with a cross-sectional study by Cybulsky et al on 1068 working-age men in Izhevsk, Russia, which reported 41% of patients taking antihypertensive drugs daily [43].…”
Section: Discussionsupporting
confidence: 80%
“…However, 180 million cases have been totally diagnosed by the end of 2015. The main treatment methods for hyperlipidemia include diet treatment, smoking cessation, and alcohol restriction, weight loss, drug treatment, of which drug therapy is the primary treatment approach [18–20] . However, the available drug treatment on the market shows the disadvantages of a long cycle and various adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study carried out in Russia showed that BP control was maintained in 17% of patients out of 66% of patients with dual diagnoses of dyslipidemia and HTN who remained aware of their ongoing HTN diagnosis. 47 …”
Section: Discussionmentioning
confidence: 99%